PENGARUH PENGETAHUAN PERPAJAKAN, SANKSI PAJAK, KESADARAN PERPAJAKAN DAN TINGKAT PENDIDIKAN TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM PEMENUHAN KEWAJIBAN PAJAK - Kusuma, Rangga Rian Wira Ari; Achmad, Hadli; Masamah, Masamah (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2021)
This study aims to determine the effect of tax knowledge, tax sanctions, tax awareness and education level on the motivation of individual taxpayers in fulfilling tax obligations. This study uses quantitative research using primary data obtained from questionnaires. The population in this study is the individual taxpayer registered at the Palembang Ilir Timur Tax Office Pratama. In this study the sampling using the Non Probability Sampling method and sampling technique using the Slovin method, with a population of 156,145 people and a minimum sample of 100 respondents can be taken.